The Implementation and Effect of Problem-Based Learning Based on Local Wisdom Toward Students’ Communication and Critical Thinking Ability on Temperature and Heat Topic - Suci Kartika Suci; Muhaimin Muhaimin; Zurweni Zurweni (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
The researcher conducted the research to determine the effect of implementing the problem-based learning model based on local wisdom on the students’ communication and critical thinking ability. This type of research was quasi-experimental using a pretest-posttest nonequivalent control design. The research population was students of class XI science Senior High School 5 Jambi City with a sample of two classes, namely the experimental and control classes. The researcher used the data collected using a test instrument measuring students’ written communication and critical thinking. The researcher used the observation sheet instrument to measure students’ oral communication. Data analysis techniques are descriptive and inferential to test the hypothesis. Inferential analysis using independent sample t-test, paired t-test and manova test. The results of the descriptive analysis of the average pretest using 33.06 and 29.33 test questions in the experimental class while the control class on each test item is 31.71 and 24.65. The average results of post-test scores after implementing the problem-based learning model based on local wisdom on written communication and critical thinking were 59.07 and 57.06 in the experimental class, while in the control class 44.68 and 35.19. The inferential analysis of the problem-based learning model based on local wisdom has a good influence on oral, written communication and critical thinking. There are differences in students’ communication and critical thinking using a problem based learning model based on local wisdom showing good results. There is a simultaneous influence on oral, written and critical thinking communication skills by implementing a problem based learning model based on local wisdom.